Novel SMPS with Good Power Factor Correction Method - Smt. Sujata R. Nagargoje, Prof. Milind Marathe (International Journal of Advanced Science and Technology, 2020)
When input current of power supply is in synchronization with input mains voltage and current waveform is sine wave then we will get maximize power drawn from the mains and power factor correction will reduce losses in distribution system, it reduces electricity bill means it's a cost saving factor.We suggested new way to implement boost converterbasedSMPS,ActualdesignofSMPSwith PFC is complicated problem and by using TI UCC28019A IC is not tested by manypeople.